2001
DOI: 10.1074/jbc.m009780200
|View full text |Cite
|
Sign up to set email alerts
|

The Long and the Short Cycle

Abstract: The C terminus of the human V2 vasopressin receptor contains multiple phosphorylation sites including a cluster of amino acids that when phosphorylated prevents the return of the internalized receptor to the cell surface. To identify the step where the recycling process was interrupted, the trafficking of the V2 receptor was compared with that of the recycling V1a receptor after exposure to ligand. Initially, both receptors internalized in small peripheral endosomes, but a physical separation of their endocyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 32 publications
2
62
0
Order By: Relevance
“…There is increasing evidence the C-tails of GPCRs are important determinants in regulating their endosomal trafficking (33)(34)(35)(36). For the C-tail of ␤ 2 AR, tyrosine 350 and 354 are required for receptor down-regulation (9), and the terminal four amino acid residues (DSLL) represent a PDZ domain binding motif that is involved in the sorting of ␤ 2 AR between recycling endosomes and lysosomes (34,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence the C-tails of GPCRs are important determinants in regulating their endosomal trafficking (33)(34)(35)(36). For the C-tail of ␤ 2 AR, tyrosine 350 and 354 are required for receptor down-regulation (9), and the terminal four amino acid residues (DSLL) represent a PDZ domain binding motif that is involved in the sorting of ␤ 2 AR between recycling endosomes and lysosomes (34,36).…”
Section: Discussionmentioning
confidence: 99%
“…Role of the C-tail of ␤AR in Agonist-mediated Regulation-As the C-tails of a number of GPCRs have been identified as structural determinants in targeting the receptors to lysosomes (33)(34)(35), we explored the effect of replacing the C-tail of one subtype with that of the other on agonist-mediated regulation. As the first step in the regulatory process is receptor phosphorylation, we 32 P-labeled BHK cells transiently expressing ␤ 1 AR, ␤ 2 AR, or the chimeras, ␤ 1 /␤ 2 ct-AR and ␤ 2 /␤ 1 ct-AR, stimulated the cells with agonist, and purified and analyzed the receptors for 32 P incorporation (Fig.…”
Section: Effects Of Blocking Trafficking To Lysosomes On Basal and Agmentioning
confidence: 99%
See 1 more Smart Citation
“…The recycling pathway appears to be the default pathway for membrane proteins that are not trafficked to the lysosomal pathway (11). Although this view is generally true for the constitutively internalized and recycled molecules, such as transferrin, recent studies have indicated that recycling of internalized GPCRs is regulated (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Mutagenesis of single serines or threonines in the C-terminal tail reduced phosphorylation to different degrees and had variable effects on V2R recycling 8,19 . Ser 255 represents the first phosphorylation site identified in the 3 rd intracellular loop of V2R (Figure 3).…”
Section: Results and Disscussionmentioning
confidence: 99%